The Living Classroom Experiential Pedagogy as a Soft Power Strategy in Green Tourism Diplomacy at the Batur UNESCO Global Geopark Museum - Anggayana, I Wayan Agus; Osin, Rosvita Flaviana; Suryawati, Dewa Ayu; Wiramatika, I Gede; Dewi, Si Putu Agung Ayu Pertiwi; Angginingsih, Ni Nyoman Novita (International Journal of Sustainable Competitiveness on Tourism, 2026)
This study examines the Batur UNESCO Global Geopark Museum as a case study for green tourism diplomacy. Through a qualitative analysis of an in-depth interview with the museum's management, the paper argues that the museum's reliance on experiential learning pedagogy is not merely an educational tool but a potent soft power strategy. This approach transforms the museum into an arena for cultivating environmental stewardship, thereby projecting an image of Indonesia as a nation committed to sustainability and progressive education. The analysis reveals how the museum bridges formal and informal learning by integrating its programs into the school curriculum, leverages the cognitive power of direct, concrete experience to deepen understanding of natural and cultural heritage, and employs a pedagogical language aimed at nurturing intrinsic motivation for conservation. The findings suggest that the museum's educational model functions as a localized, authentic, and highly effective instrument of public diplomacy. It cultivates a generation of domestic ambassadors for sustainability and communicates a national identity rooted in environmental responsibility and educational innovation. This positions the museum's model as a replicable strategy for other heritage sites aiming to leverage education for diplomatic and nation-branding purposes within the framework of sustainable tourism.